1992
DOI: 10.2307/3676427
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Visual Recruitment by Seabirds to Ephemeral Foraging Flocks

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . Wiley-Blackwell and Nordic Society Oikos are collaborating with JSTOR to digitize, preserve and extend access to Ornis Scandinavica. . 1992. Geometry of visual recruitment by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 47 publications
(27 reference statements)
4
58
0
Order By: Relevance
“…Having spent most of their year a long way from the CCS, once birds have found highly productive waters, through olfaction perhaps, they could use visual cues to locate actual prey schools (Haney et al, 1992;Nevitt, 1999c). Although it is possible that nonProcellariiform species were attracted also to the sight of other foraging birds (Hoffman et al, 1981;Maniscalco et al, 1998), this idea was not well supported by the PCA analyses showing only weak associations between most species representing the two groups.…”
Section: Relationships To Physical and Biological Variablesmentioning
confidence: 51%
“…Having spent most of their year a long way from the CCS, once birds have found highly productive waters, through olfaction perhaps, they could use visual cues to locate actual prey schools (Haney et al, 1992;Nevitt, 1999c). Although it is possible that nonProcellariiform species were attracted also to the sight of other foraging birds (Hoffman et al, 1981;Maniscalco et al, 1998), this idea was not well supported by the PCA analyses showing only weak associations between most species representing the two groups.…”
Section: Relationships To Physical and Biological Variablesmentioning
confidence: 51%
“…showed that the mean recruitment distance to ephemeral foraging flocks was 4.5 km but could reach 20 km (Haney et al, 1992). For a social bird, the distance over which it can detect thermals will be further than for a non-social bird, see the thermal and bird detection limits in Table 2.…”
Section: Submodelsmentioning
confidence: 99%
“…Unlike some terrestrial birds and aquatic birds such as pelicans and avocets (del Hoyo et al 1992(del Hoyo et al , 1995, pelagic seabirds have not generally been observed to cooperate in groups when searching for and capturing prey. Instead, large aggregations of feeding seabirds are believed to result from the accumulation of independent foragers at prey patches (Hoffman et al 1981, Duffy 1989, Harrison et al 1991, Haney et al 1992, Shealer 2002. One important cue that pelagic seabirds use to find prey may be the behavior of other seabirds, a strategy called local enhancement (e.g.…”
Section: Introductionmentioning
confidence: 99%